Understanding hydration heat of mortars containing supplementary cementitious materials with potential to immobilize heavy metal containing waste. (January 2021) - Phung, Quoc Tri; Ferreira, Eduardo; Seetharam, Suresh; Nguyen, Van Tuan; Govaerts, Joan; Valcke, Elie
Abstract: Supplementary cementitious materials (SCMs) have been widely used not only in civil engineering concrete components, but also in (nuclear) waste treatment engineering because of their beneficial effects on microstructure, engineering properties and durability of concrete. A comprehensive experimental campaign has been undertaken to investigate the effects of SCMs, which includes silica fume (SF) and blast furnace slag (BFS) in combination with ordinary Portland cement (OPC) on the behaviour of hydration heat evolution during early ages of mortars. The samples with different water/cement (w/c) ratios (0.5, 0.7, 0.9) and replacement ratios of SF (10%, 20%, 30%) and BFS (30%, 50%, 70%) were subjected to isothermal calorimetry tests at various temperatures (20, 30, 40 and 50 °C) in order to assess the effects of SCMs on the rate of hydration heat, cumulative heat release, activation energy and setting times of blended mortars. Knowledge obtained from these blended systems was then applied for cementation of a heavy metal containing waste sludge simulant, where the potential for thermal cracking and delayed ettringite formation due to hydration heat generation is of great concern. Results show that both BFS and SF increase the hydration rate but reduce cumulative heat release compared to pure OPC mortar. The ternary system (OPC:BFS:SF) exhibits different hydration characteristics compared to the binary system (OPC:BFS(or SF)) and there is a slight interaction between BFS and SF. The presence of sludge in the matrix significantly accelerates the hydration process and reduces the apparent activation energy. The role of temperature is more important for mortars containing BFS rather than SF, and less pronounced for the system containing sludge. Estimating the setting times based on the isothermal calorimetry data is more accurate for the final setting time rather than for initial setting time and an overestimation of 10% might occur or even more for the system containing sludge, which is still acceptable taking into account the measurement uncertainty. Highlights: Comprehensive experiments have been performed to highlight underlying hydration mechanisms and possible synergy effects. There is a slight interaction between blast furnace slag and silica fume. Temperature role is more important for mortars containing BFS than SF, and less pronounced for system containing sludge. Apparent activation energy (Ea ) of ternary system is higher than binary system, while sludge helps to reduce Ea . New method was proposed to estimate the setting times based on the isothermal calorimetry data.